(untitled) (Anclajes, 2021)
This article explores the particularities of self-translation and retranslation practices in contemporary Mapuche poetry, based on a case study: the bilingual poem Chonkitun by Leonel Lienlaf, retranslated to Mapuzungun by Víctor Cifuentes. Through a comparative analysis of the Spanish and Mapuzungun versions of the work in question, we discuss and reflect on the parameters of innovation, fidelity and authenticity that self-translator and retranslator use in the process of writing and translating the poem, with special attention to its context of production and editing and to the subalternized condition of the Mapuche language and its place in the contemporary Mapuche literary system.